The influence of a pre-exercise sports drink (PRX) on factors related to maximal aerobic performance - Mooneyhan Andy; Simpson Warren; Keith Susan; Byars Allyn; Greenwood Mike (Taylor & Francis Group, 2010)
Abstract Background Pre-exercise sports drinks (PRX) are commonly used as ergogenic aids in athletic competitions requiring aerobic power. However, in most cases, claims regarding their effectiveness have not been substantiated. In addition, the ingredients in PRX products must be deemed acceptable by the athletic governing bodies that regulate their use in training and competition. The purpose of this study was to examine the effects of a modified PRX formulation (known as EM·PACT™) from earlier investigations on factors related to maximal aerobic performance during a graded exercise test. The modification consisted of removing creatine to meet the compliance standards set forth by various athletic organizations that regulate the use of nutritional supplements. Methods Twenty-nine male and female college students varying in levels of aerobic fitness participated in a randomized crossover administration of PRX (containing 14 g/serving of fructose, medium-chain triglycerides, and amino acids mixed with 8 oz. of water) and placebo (PL) 30 minutes prior to performing a treadmill test with approximately one week separation between the trials. VO2max, maximal heart rate (HR), time to exhaustion (Time), and percentage estimated non-protein fat substrate utilization (FA) during two a priori submaximal stages of a graded exercise testing were evaluated. Results The VO2max mean value of the PRX trial was significantly greater than the PL trial (P < 0.01). The mean value for Time was also observed to be greater for the PRX trial compared to PL (P < 0.05). Additionally, percentage of FA during submaximal stages of the exercise test was greater for PRX trial in comparison to PL (P < 0.01). Conclusions The modified PRX formulation utilized in this investigation supports the findings of the previous investigation and its efficacy for enhancing indices of aerobic performance (specifically VO2max, Time, & FA) during graded exercise testing.